Judicial management in Botswana : is it time for change? - Mmopi, Peo Malaika (Department of Commercial Law, 2016)
A company is an integral part of society whose existence impacts the country's economy and community as a whole, thus, the previous global financial crisis has highlighted the need for countries to have effective mechanisms to support and encourage corporate rescue. This is important because companies that encounter financial or economic collapse are able to benefit from corporate rescue mechanisms which may help preserve their on - going viability. In this regard, the turnaround of such companies will enable restoration of production capacity, employment, and the promotion of sustainability of capita l and investments. However, existing legal frameworks on corporate rescue in many countries have been found to be wanting, and this has in turn triggered a new wave of legislative reform proposals. Thus, the aim of this dissertation is to interrogate into the issue of whether there is a need for Botswana to reform its insolvency laws in order to accommodate a modernised corporate rescue regime. This dissertation probes on the shortcomings of judicial management as a corporate rescue regime which is currently operative in Botswana. Furthermore, the study reveals the performance of judicial management as a regime in other countries in order to illustrate its inherent weaknesses. This study makes a comparison of the main components that make up modern corporate rescue regimes in order to be able to identify critical issues to be considered in making recommendations for legislative reform. Overall the study recommends the reform of the judicial management laws in Botswana by integrating the positive aspects of corporate rescue as applied in other countries as illustrated by examples of Australia, the United Kingdom and South Africa, and avoiding the pitfalls so far proving a burden in these jurisdictions. The reform should also make adjustments accordingly as relevant to the existing business environment and the economy as well as develop new provisions to cover social conditions unique to Botswana.